Perbaikan Berat Badan Tikus Model Diabetes setelah Pemberian Media Terkondisi Sel Punca Mesensimal (MT-SPM) - Ida Ayu Preharsini Kusuma (Journal of Scientech Research and Development, 2023)
This study aims to determine the effect of Mesenchymal Stem Cell Conditioned Medium (MSC-CM) on body weight improvement in type 2 DM rats Rattus Norvegicus, Sprague Dawley strain. Experimental animals were clustered into three groups. The first group as a control (-) that was without STZ and NA induction, the second group as a control (+) was induced by STZ 60 mg/kgBW plus NA 120 mg/kgBW, and the treatment group (P) was induced by STZ and NA then given MT- SPM 0.1 mL/200 g BW intraperitoneally (i.p) once every three days for 30 days. Based on the Independent T-test, a p-value <0.001 or p <0.05 was obtained, so it was concluded that there was a significant difference in body weight in each group. The results showed an increase in body weight in the treatment group (P) compared to the control group (+). Thus, the administration of MSC-CM can improve the condition of type 2 DM by increasing body weight in type 2 DM rat models.